Sustaining Life on Earth: Environmental and Human Health through Global Governance - Soskolne Colin L.; Westra Laura; Kotze Louis J.; Mackey Brendan; Rees William E.; Westra Richard (Lanham Boulder New York Toronto Plymouth Lexington Books Rowman & Littlefield Publishers, Inc., 2008)
As global warming, famine, and environmental catastrophes have become daily news items, achieving a sustainable environment to maintain the future of life on Earth has become a global concern. Sustaining Life on Earth is an important contribution toward assessing such problems and making the Earth hospitable to life for generations to come. With an interdisciplinary team of international scholars, this masterfully edited collection approaches the problems facing sustainability from a perspective of global governance. To date, powerful economic forces have misguided decision-making processes in favor of short-term gain rather than long-term sustainability. As global awareness has increased and individual citizens have begun to alter their lifestyles to be more environmentally conscious, it is also necessary for governing bodies to take these concerns seriously. Sustaining Life on Earth makes the case that, for all the recent neo-liberal emphasis on the autonomous individual, humanity has collective problems, and it is only through collective action that solutions will be found. It shows that the global community is beginning to acknowledge the interdependencies among population, affluence, and technology. In the book, analysts from many disciplines advance solutions that could shift us away from growth-bound status quo development approaches toward more ecologically responsible and socially equitable ways of living. They suggest ways to move forward that would ensure health and well-being for all in both present and future generations. While success necessarily entails many changes at all levels, the book highlights one soft-law instrument that reflects many of the values and principles necessary to set humanity onto a sustainable path: The Earth Charter of 2002. Sustaining Life on Earth is a ground-breaking contribution to the burgeoning study of sustainability. Designed for a general non-specialist readership in the first year of university or beyond, this book will be of interest to anyone concerned with the impacts of global change on human well-being and the ecosphere, including people in environmental NGOs and those working in public policy.
Keywords: 502 .